ChemInform Abstract: Enamide Derivatives: Versatile Building Blocks for Highly Functionalized α, β‐Substituted Amines. Issue 10 (March 2015) - Bernadat, Guillaume; Masson, Geraldine
Abstract Review: [93 refs.